Anthropometry Description In Households That Experiences Obesity - Muriyati; Ilhamsyah; Suhartini Nur (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2020)
Obesity is defined as abnormal or excessive fat accumulation that can interfere with health. In 2015, more than 1.9 billion adults were overweight and 400 million of them were obese. Various types of anthropometry can be used to determine the occurrence of obesity, these methods include measurement of body mass index (BMI). Arm circumference, and abdominal circumference. Body mass index is an indicator of obesity that is widely used to estimate the composition of body fat. Based on an initial survey conducted in April-May the number of obesity increased until June-July 2018. From the results of a preliminary study conducted by researchers, more productive-age housewives were obese I than obesity II. An anthropometric picture of obese housewives in Taccorong Village, Bulukumba District was known. The method used in this research is descriptive with a simple approach. Sampling was carried out with a purposive sampling technique. The population in this study was 1,011 people. The sample in this study was 62 respondents. The results of this study indicate that housewives of productive age who have a picture (obesity I) BMI 25-29.9 amounted to 59.7%, and (obesity II) BMI ≥ 30 by 40.3%, normal upper arm circumference of 24, 2%, abnormal upper arm circumference 75.8%, and abdominal circumference 62%. The conclusion of this study is that housewives who are obese in Taccorong Village, Bulukumba Regency are based on productive age (15-49) years old, with young adults (18-35) years totaling 37 (59.7%) respondents and old adulthood (36-49 ) year totaling 25 (40.3%) respondents. It is recommended for housewives to improve a healthy lifestyle to avoid obesity which can lead to degenerative diseases.